(3SMQ GdYbds (3cja JWhQ echfGJ GdPcGA GdKdGKI GdCcKQ CgejI aj YGde Gdjhe(B=How to develop the 3 components of intelligence that matter most in today's worlds - (3ejdQ, Lhf dhQGfSs; (3ecJHI LQjQs ((3GdQjGVs (3ecJHI LQjQs, 2010)
(3jSJfO gPG GdcJGH Gdi fXQjI (B"(3HjGLjg(B" (3ddfeh GdeYQaj h GdJWhQ GdEOQGcjs
1 11 13
Keywords: (3GdEOQGcs; (3GdJacjQs; (3GdPcGAs; (3GdYbd h GdLSes; (3GdYbds